2020
DOI: 10.1111/odi.13758
|View full text |Cite
|
Sign up to set email alerts
|

An association analysis for genetic factors for dental caries susceptibility in a cohort of Chinese children

Abstract: Objective To comprehensively investigate the effects of 25 variants in 15 genes on dental caries susceptibility in a cohort of Chinese children. Methods A total of 25 variants in 15 genes were genotyped with MassARRAY iPLEX system and analyzed in 265 healthy controls and 254 children affected by dental caries with different dmft scores. The children with dental caries were stratified into “mild group” (scores from 1 to 3), “moderate group” (scores from 4 to 6), and “severe group” (scores from 7 to 14). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
0
6
2
Order By: Relevance
“…However, the above three classical association analysis algorithms have the following problems: all three association analysis algorithms are based on a common minimum support framework; that is, the application decision-maker needs to artificially set minimum support to ensure that frequent itemsets can be filtered out in each iteration, which follows the a priori property, also known as the downward closure property, that any subset of frequent itemsets must be frequent [ 7 ]. The above minimum support framework also poses an important problem for the application of the algorithm: in order to be able to propose suitable minimum support, the decision-maker needs to have sufficient goal knowledge and detailed prior knowledge about the target task and to be able to accurately predict the number of rules to be generated before the mining work is completed [ 8 ]. In addition, the minimum support setting itself is very delicate; if it is set too small, the algorithm will return a large number of frequent patterns, most of which may be a priori stale knowledge or uninteresting mining results; if it is set too large, the algorithm may fail to generate patterns [ 9 ].…”
Section: Related Workmentioning
confidence: 99%
“…However, the above three classical association analysis algorithms have the following problems: all three association analysis algorithms are based on a common minimum support framework; that is, the application decision-maker needs to artificially set minimum support to ensure that frequent itemsets can be filtered out in each iteration, which follows the a priori property, also known as the downward closure property, that any subset of frequent itemsets must be frequent [ 7 ]. The above minimum support framework also poses an important problem for the application of the algorithm: in order to be able to propose suitable minimum support, the decision-maker needs to have sufficient goal knowledge and detailed prior knowledge about the target task and to be able to accurately predict the number of rules to be generated before the mining work is completed [ 8 ]. In addition, the minimum support setting itself is very delicate; if it is set too small, the algorithm will return a large number of frequent patterns, most of which may be a priori stale knowledge or uninteresting mining results; if it is set too large, the algorithm may fail to generate patterns [ 9 ].…”
Section: Related Workmentioning
confidence: 99%
“…The studies by Ozturk, Yildiz and Wu supported this hypothesis. They found that carriers of the DEFB1 rs11362 TT genotype had a higher risk of caries [ 19 , 21 , 22 ]. A meta-analysis published in 2020 also showed that individuals with the TT genotype had a seven times higher risk of caries in permanent dentition than individuals with the CC genotype [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between the DEFB1 rs11362 polymorphism and caries was observed in some populations. Carriers of the DEFB1 rs11362 T allele have a higher risk of caries than carriers of the C allele, as documented in studies of children from Ribeirão Preto in Brazil [ 20 ] and Gansu Province in China [ 19 ], as well as in adults from Turkey [ 21 ] and North America [ 22 ]. In contrast, studies examining Italian adults and Latvia children with cleft lip suggested that CC genotype carriers have a higher risk of caries [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural antimicrobial peptides are potential biomarkers because deregulation of antimicrobial peptides can affect the caries risk (Jurczak et al, 2015;Munther, 2020) or are genetic susceptibility markers of caries (Slebioda et al, 2020;Wu et al, 2020). It is suggested that a positive correlation exists between the salivary hBD-2 level and caries progression (Jurczak et al, 2015).…”
Section: Natural Antimicrobial Peptidesmentioning
confidence: 99%